Nanosilver inhibits the progression of pancreatic cancer by inducing a paraptosis-like mixed type of cell death - Liu, Li; An, Xuefeng; Schäfer, Michael; Yan, Bin; Torre, Carolina de la; Hillmer, Stefan; Gladkich, Jury; Herr, Ingrid (Biomedicine & pharmacotherapy, 2022)
Silver has been in clinical use since ancient times and silver nanoparticles (AgNPs) have attracted attention in cancer therapy. We investigated the mechanisms by which AgNPs inhibit pancreatic ductal adenocarcinoma (PDAC). AgNPs were synthesized and 3 human PDAC and 2 nonmalignant primary cell lines were treated with AgNPs. MTT, MAPK, colony, spheroid and scratch assays, Western blotting, TEM, annexin V, 7-AAD, and H2DCFDA staining, FACS analysis, mRNA array and bioinformatics analyses, tumor xenograft transplantation, and immunohistochemistry of the treated cells were performed. We found that minimal AgNPs amounts selectively eradicated PDAC cells within a few hours. AgNPs inhibited cell migration and spheroid and colony formation, damaged mitochondria, and induced paraptosis-like cell death with the presence of cytoplasmic vacuoles, dilation of the ER and mitochondria, ROS formation, MAPK activity, and p62 and LC3b expression, whereas effects on the nucleus, DNA fragmentation, or caspases were not detectable. AgNPs strongly decreased tumor xenograft growth without side effects and reduced the expression of markers for proliferation and DNA repair, but upregulated paraptosis markers. The results highlight nanosilver as complementary agent to improve the therapeutic efficacy in pancreatic cancer.